Exploring School-Based Civic Engagement for Enhancing Life Satisfaction in the Baduy Indigenous Community - Rizal Fahmi; Karim Suryadi; Siti Nurbayani K; Asep Mahpudz (AL-ISHLAH: Jurnal Pendidikan, 2025)
Life satisfaction is a critical indicator of democratic governance, reflecting citizens’ well-being and their active participation in societal development. However, prior studies often emphasize government responsibility, neglecting the role of citizen-driven initiatives—particularly in Indigenous contexts such as the Baduy community in Indonesia. This study adopts a narrative literature review method to examine the potential of school-based civic engagement in enhancing life satisfaction among the Baduy people. Relevant peer-reviewed articles published between 2015 and 2024 were sourced from Scopus, ScienceDirect, DOAJ, and Google Scholar. The selection process involved screening, eligibility assessment, and thematic synthesis of 27 studies focused on civic engagement, life satisfaction, and Indigenous well-being. The findings suggest that civic engagement, facilitated through educational institutions, fosters community participation, social cohesion, and cultural preservation. In Indigenous contexts, such as the Baduy community—renowned for their local wisdom, ecological values, and self-reliance—civic practices aligned with traditional norms can enhance subjective well-being. Engagement models involving collaborative education, service learning, and institutional partnerships emerged as promising strategies. School-based civic engagement offers a culturally responsive and sustainable alternative to state-centric development approaches. For the Baduy, integrating civic values into education may strengthen communal identity while promoting life satisfaction. These insights underscore the need for inclusive civic education models tailored to Indigenous contexts, with implications for policymakers, educators, and future research.